Petilasan Prabu Brawijaya V di Alas Ketonggo Srigati Ngawi - Dian Rahma nur Afifah (LP4MK STKIP PGRI Lubuklinggau, 2021)
Alas Ketonggo Srigati Ngawi still keeps various oral works, namely oral works that are trusted by local residents and are spoken or passed down from generation to generation. And also still harboring its thickness, namely various mythical things with traditions that are deeply believed by local residents. As part of history, there is one of the literatures, namely oral literature which holds a lot of information related to past events, oral literature has become a pride and has even become the identity of each region. There are three cultural values, namely: Values ​​related to human life as social beings, values ​​related to human life as individual beings, and values ​​related to human life as God's creatures. The influence of the myth of Alas Ketonggo Srigati on society includes: forming character, belief, and nature or action in human life. Alas Ketonggo Srigati this place is a historic place because in ancient times Alas Ketonggo Srigati was the resting place for King Brawijaya V who fled from the Majapahit Kingdom because he was being attacked by the Demak Army. At that time, the Demak army was under Raden Patah's control. Not only that, King left his oversized clothes in that place. This was done before he left for Mount Lawu to meditate. Located in Brendil Hamlet, Hutan, Babadan, Paron District, Ngawi Regency.